Ovarian Cystadenomas: Growth Rate and Reliability of Imaging Measurements. (30th November 2021) - Suh‐Burgmann, Elizabeth; Nakhaei, Masoud; Gupta, Sonia; Brook, Alexander; Hecht, Jonathan; Hung, Yun‐Yi; Levine, Deborah
Abstract : Objectives: To evaluate the growth rate of benign ovarian cystadenomas and the degree of variability in ultrasound measurements. Methods: Two independent retrospective cohorts of women found to have benign cystadenomas at surgery were identified. To assess growth rate, ultrasounds on women in a community‐based health system were reviewed and the growth rate was determined based on the maximum reported size dimension using a mixed effect model. To assess measurement variability, two radiologists independently measured presurgical adnexal imaging findings for women in a tertiary care referral setting. Interobserver, intra‐observer, and intermodality (cine clip versus still images) variability in measurements was determined using correlation coefficients (CC) and Bland–Altman analysis, with the proportion of measurements varying by more than 1 cm calculated. Results: For growth rate assessment, 405 women with 1412 ultrasound examinations were identified. The median growth rate was 0.65 cm/year with mucinous cystadenomas growing faster at 0.83 cm/year compared to 0.51 cm/year for serous cystadenomas (median test P < .0001). To evaluate measurement variability, 75 women were identified with 176 ultrasound studies. The within‐subject standard deviations for ultrasound measurements were 0.74 cm for cine clip images and 0.41 cm for static images, with 11% of measurements overall differing by more than 1 cm. Conclusions: Cystadenomas grow on average 0.65 cm/year, which is similar in magnitude to the inherent error observed in measurement on ultrasound, suggesting that repeat ultrasound at intervals of longer than a year will often be needed to accurately assess growth if a cyst represents a benign cystadenoma.